2013
DOI: 10.1186/1465-9921-14-33
|View full text |Cite
|
Sign up to set email alerts
|

Smoking decreases the response of human lung macrophages to double-stranded RNA by reducing TLR3 expression

Abstract: BackgroundCigarette smoking is associated with increased frequency and duration of viral respiratory infections, but the underlying mechanisms are incompletely defined. We investigated whether smoking reduces expression by human lung macrophages (Mø) of receptors for viral nucleic acids and, if so, the effect on CXCL10 production.MethodsWe collected alveolar macrophages (AMø) by bronchoalveolar lavage of radiographically-normal lungs of subjects undergoing bronchoscopies for solitary nodules (n = 16) and of vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 88 publications
1
29
0
Order By: Relevance
“…In vivo, CS augments the expression and responses of TLR3 in human macrophages (18) and in murine lung tissue. However, two research groups have reported that smoking decreased TLR3 induction in human lung macrophages and NEC (13,33). In our previous study, we also found a modest increase in TLR3 in human lung during IAV infection that was inhibited by CSE (35).…”
Section: Discussionmentioning
confidence: 57%
“…In vivo, CS augments the expression and responses of TLR3 in human macrophages (18) and in murine lung tissue. However, two research groups have reported that smoking decreased TLR3 induction in human lung macrophages and NEC (13,33). In our previous study, we also found a modest increase in TLR3 in human lung during IAV infection that was inhibited by CSE (35).…”
Section: Discussionmentioning
confidence: 57%
“…After publication of these results, supplemented by a collaborative study of several cohorts indicating that airflow limitation but not CMH was strongly related to mortality (4), research interest in CMH and recurrent respiratory infections diminished for some years, and the main research focus was directed toward studies of airflow limitation. Yet, based on longitudinal observations of cohorts of working men from Paris, Kauffmann and Annesi suggested that presence of mucus hypersecretion was perhaps not as innocent as described by Fletcher and colleagues (5,6). This notion was further supported by Copenhagen studies showing a nontrivial association between CMH and FEV 1 decline and death from obstructive lung disease (7)(8)(9).…”
Section: Cd8mentioning
confidence: 95%
“…Nonetheless, could acquired (or perhaps minor genetic) defects in mucosal immunity also make patients with COPD simply less able to eliminate incipient VLRTIs? Smoking definitely decimates lung innate immune defenses (5), including antiviral recognition (6). Yet COPD can clearly progress, despite decades of smoking cessation.…”
Section: Cd8mentioning
confidence: 99%
“…Clinical characteristics of the human volunteers are shown in Table 1. Subjects underwent bronchoscopy under moderate conscious sedation using a fiberoptic bronchoscope and resident human AMø were isolated by segmental bronchoalveolar lavage, both as recently described in detail (41). Not all subjects were used in every experiment.…”
Section: Methodsmentioning
confidence: 99%